Cerkiew św. Mikołaja jako element zachowania tożsamości ludności prawosławnej w Zielonej Górze = St. Nicholas church as the element of preserving the identity of the orthodox people in Zielona Góra - Dudra, Stefan (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The foundation of the orthodox parish in Zielona Góra was connected with the removalof Ukrainians and Lemko people due to the ?Wisła? operation in 1947. The origins of the parish go back to mid-1948, when the people started to look for a building for the church. Mikołaj Proniński was the founder and the first priest of the parish in Zielona Góra. The first Holy Mass was celebrated on 8th September 1948 in a post-evangelical chapel in 5 Wąska Street. In the first years of the existence of the parish there were about 200 parishioners.
Keywords: Zielona Góra; prawosławie - historia - Polska - od 1944 r.; tożsamość